Decline in Proliferation and Immature Neuron Markers in the Human Subependymal Zone during Aging: Relationship to EGF- and FGF-Related Transcripts - Weissleder, Christin; Fung, Samantha J.; Wong, Matthew W.; Barry, Guy; Double, Kay L.; Halliday, Glenda M.; Webster, Maree J.; Weickert, Cynthia Shannon (Frontiers in Aging Neuroscience, 2016)
Neuroblasts exist within the human subependymal zone (SEZ); however, it is debated to what extent neurogenesis changes during normal aging. It is also unknown how precursor proliferation may correlate with the generation of neuronal and glial cells or how expression of growth factors and receptors may change throughout the adult lifespan. We provided evidence of dividing cells in the human SEZ in conjunction with a dramatic age-related decline (n=50; 21-103 years) of mRNAs indicative of proliferating cells (Ki67) and immature neurons (doublecortin). Microglia mRNA (ionized calcium-binding adapter molecule 1) increased during aging, whereas transcript levels of stem/precursor cells (glial fibrillary acidic protein delta and achaete-scute homolog 1), astrocytes (vimentin and glial fibrillary acidic protein) and oligodendrocytes (oligodendrocyte lineage transcription factor 2) remained stable. Epidermal growth factor receptor (EGFR) and fibroblast growth factor 2 (FGF2) mRNAs increased throughout adulthood, while transforming growth factor alpha (TGFα), EGF, Erb-B2 receptor tyrosine kinase 4 (ErbB4) and FGF receptor 1 (FGFR1) mRNAs were unchanged across adulthood. Cell proliferation mRNA positively correlated with FGFR1 transcripts. Immature neuron and oligodendrocyte expression positively correlated with TGFα and ErbB4 mRNAs, whilst astrocyte transcripts positively correlated with EGF, FGF2 and FGFR1 mRNAs. Microglia mRNA positively correlated with EGF and FGF2 expression. Our findings indicate that neurogenesis in the human SEZ continues well into adulthood, although proliferation and neuronal differentiation may decline across adulthood. We suggest that mRNA expression of EGF- and FGF-related family members do not become limited during aging and may modulate neuronal and glial fate determination in the SEZ throughout human life.